INOVASI QR CODE PADA PENCETAKAN DOKUMEN DATA PENDUDUK SEBAGAI WUJUD PENERAPAN ASAS PENYELENGGARAAN PEMERINTAHAN - Husni Mubaroq; Nurul Jannah Lailatul Fitria (Jurnal Ilmu Pemerintahan Widya Praja, 2021)
The Indonesian government has made reforms to the system of governance. Included in the system of administration of government administration. This form of renewal is by optimizing the use of information and communication technology which is increasingly sophisticated and coupled with an internet base. This renewal is called innovation with elements of technological sophistication, bringing the Indonesian government as a form of bureaucratic digitization or E-government. One of these reforms or innovations is in the Population Administration sector. The Directorate General of Dukcapil has the innovation of implementing document printing by adding a QR Code. The goal is to make public services in the population administration sector easier, better, and consistent with the principle of protecting population data. This study will describe the QR Code innovation on population documents in accordance with the principles of governance in Probolinggo City. This research method applies descriptive-oriented qualitative. The data input method is by observing phenomena related to the object of research and obtaining data from literature studies. So that it can be seen that the QR Code is a form of innovation by the Probolinggo City government in public services in the population administration sector in accordance with the legislation containing the principles of governance. Key Words: Population Administration, Barcodes, Public service.